Drug pricing reform in China: analysis of piloted approaches and potential impact of the reform. Issue 1 (1st January 2016) - Chen, Yixi; Hu, Shanlian; Dong, Peng; Kornfeld, Åsa; Jaros, Patrycja; Yan, Jing; Ma, Fangfang; Toumi, Mondher
Abstract : Objectives: In 2009, the Chinese government launched a national healthcare reform programme aiming to control healthcare expenditure and increase the quality of care. As part of this programme, a new drug pricing reform was initiated on 1 June 2015. The objective of this study was to describe the changing landscape of drug pricing policy in China and analyse the potential impact of the reform. Methods: The authors conducted thorough research on the drug pricing reform using three Chinese databases (CNKI, Wanfang, and Weipu), Chinese health authority websites, relevant press releases, and pharmaceutical blogs and discussion forums. This research was complemented with qualitative research based on targeted interviews with key Chinese opinion leaders representing the authorities' and prescribers' perspectives. Results: With the current reform, the government has attempted to replace its direct control over the prices of reimbursable drugs with indirect, incentive-driven influence. Although the exact implementation of the reform remains unclear at the moment, the changes introduced so far and the pilot project designs indicate that China is considering adaptation of some form of internal and external reference pricing policies, commonly used in the Organisation for Economic Co-operation and Development countries. Several challenges related to the potential new mechanism were identified: 1) the risk of hospital underfunding, if hospital funding reform is not prioritised; 2) the risk of promoting the use of cheap, low-quality drugs, if a reliable quality control system is not in place and discrepancy between the available drugs is present; 3) the risk of increasing disparity in access to care between poor and rich regions, in case of country-wide price convergence; and 4) the risk of industry underinvestment, resulting in reduced competition, issues with quality and sustainability of supply, and potentially negative social impact. Conclusions: Foreign pricing policies cannot be transferred to China without prioritising historical, cultural, and economic contextualisation. Otherwise, the new policy may be counterproductive and affect the whole healthcare chain, as well as the health outcomes of Chinese patients.